2022
DOI: 10.1177/10556656221100125
|View full text |Cite
|
Sign up to set email alerts
|

Cephalometric Soft Tissue Morphology of Adults With Unoperated Submucous Cleft Palate

Abstract: The aim of this study was to compare craniofacial soft tissue characteristics between subjects with unrepaired submucous cleft palate (SMCP) and noncleft individuals. This retrospective cross-sectional study was performed on 27 subjects with unrepaired SMCP (13 male and 14 female subjects; mean age, 21.77 ± 4.09 years) and 30 noncleft controls (14 male and 16 female subjects; mean age, 22.67 ± 4.28 years). The predictor variable was cleft deformity. The outcome variable was cephalometric soft tissue measureme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…1 However, limited previous data suggested that adults with CL/P demonstrated smaller sagittal maxillary length and inharmonious jaw relationship with a flatter facial profile, retrusive nasal base, a less prominent nasal tip, and decreased upper lip protrusion. 7,8 According to these data, correlation existed between nasal morphology and sagittal and vertical jaw configuration in various subtypes of CL/P. The phenomena that S-N-A angle registered positive correlations with nasal base prominence, and upper facial height had positive correlations with nasal dorsum length and nasal bone length were found between the normal and patients with CL/P.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…1 However, limited previous data suggested that adults with CL/P demonstrated smaller sagittal maxillary length and inharmonious jaw relationship with a flatter facial profile, retrusive nasal base, a less prominent nasal tip, and decreased upper lip protrusion. 7,8 According to these data, correlation existed between nasal morphology and sagittal and vertical jaw configuration in various subtypes of CL/P. The phenomena that S-N-A angle registered positive correlations with nasal base prominence, and upper facial height had positive correlations with nasal dorsum length and nasal bone length were found between the normal and patients with CL/P.…”
Section: Discussionmentioning
confidence: 86%
“…Some also reported that a short and protrusive maxilla tended to accompany a shorter and straighter nose 1 . However, limited previous data suggested that adults with CL/P demonstrated smaller sagittal maxillary length and inharmonious jaw relationship with a flatter facial profile, retrusive nasal base, a less prominent nasal tip, and decreased upper lip protrusion 7,8 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations